Efficacy and safety of rucaparib in patients with recurrent high-grade ovarian carcinoma: A systematic review and meta-analysis - Nicholas Adrianto; Ghea Mangkuliguna; Eunike Jennifer Tandiono; Candra Novi Ricardo Sibarani (Elsevier, 2024)
Ovarian cancer stands as the third most prevalent gynecological malignancy. The advent of PARP inhibitors, particularly rucaparib, has revolutionized the landscape of advanced ovarian cancer treatment, demonstrating notable efficacy with minimal toxicity, especially in patients not previously exposed to PARP inhibitors. Rucaparib's precision-driven approach, targeting specific genetic mutations, disrupts DNA repair mechanisms, resulting in cytotoxic effects on neoplastic cells. This comprehensive review delves into the clinical efficacy and safety profile of rucaparib in recurrent ovarian cancer, showcasing its promising therapeutic approach. A systematic search of studies reporting rucaparib efficacy and safety, up to September 2023, was conducted across various reputable databases and sources. The meta-analysis of seven articles revealed a pooled objective response rate (ORR) of 0.331 (95% CI, 0.221-0.449; I2 = 92.4%), underscoring rucaparib's efficacy, particularly evident in the BRCA-mutated cohort. Rucaparib consistently outperformed controls in progression-free survival (PFS) and overall survival (OS). Safety evaluations indicated that 98.7% of patients experienced treatment-emergent adverse events (TEAEs), with 61% being grade ≥3. Notable TEAEs included nausea (69.0%), fatigue (66.8%), vomiting (37.3%), and constipation (32.1%). Hematological concerns comprised anemia (47.9%), thrombocytopenia, elevated AST/ALT (37.3%), and serum creatinine levels (19.7%). Despite favourable outcomes, the rucaparib group recorded higher event rates across various metrics than controls. The findings underscore the need for meticulous monitoring and dose adjustments to optimize therapeutic outcomes and mitigate the increased risks associated with adverse events. International Prospective Register of Systematic Review Identifier: CRD42023459646.